Pemahaman Wajib Pajak, Kesadaran Wajib Pajak, Sanksi Pajak, dan Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Ponorogo - Muhdor, Ali; Prayogi, Yoga Adi; Purwanti, Wiwik (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This research aims to determine the influence of taxpayer understanding, taxpayer awareness and tax sanctions on motor vehicle taxpayer compliance in Ponorogo Regency (Case study of the Ponorogo Samsat joint office). This research uses quantitative methods. The population in this study were motor vehicle taxpayers in Ponorogo Regency, while the number of samples used was 100 respondents. Hypothesis testing is used for multiple linear regression, t-test, F test, and dominant test. Partial research results show that taxpayer understanding significantly affects taxpayer compliance, taxpayer awareness significantly affects taxpayer compliance, and tax sanctions have no significant effect. Simultaneously, taxpayer understanding, taxpayer awareness, and tax sanctions significantly affect taxpayer compliance. The variable taxpayer understanding has a dominant influence on taxpayer compliance.